2016
DOI: 10.4314/mmj.v28i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of non-standard HIV antiretroviral therapy regimens at Lighthouse Trust in Lilongwe, Malawi

Abstract: AimLighthouse Trust in Lilongwe, Malawi serves approximately 25,000 patients with HIV antiretroviral therapy (ART) regimens standardized according to national treatment guidelines. However, as a referral centre for complex cases, Lighthouse Trust occasionally treats patients with non-standard ART regimens (NS-ART) that deviate from the treatment guidelines. We evaluated factors contributing to the use of NS-ART and whether patients could transition to standard regimens. MethodsThis was a cross-sectional study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Regarding the consequences of drug stockouts, several other studies in sub-Saharan Africa have suggested that medicine shortages may affect treatment and treatment outcomes [6, 14, 15]. A study in Malawi showed that one of the reasons for changing the HIV treatment regimen was drug stockouts [14]. A study in Ivory Coast found that stockouts caused 9% of the HIV treatment discontinuations and 30% of the treatment alterations.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the consequences of drug stockouts, several other studies in sub-Saharan Africa have suggested that medicine shortages may affect treatment and treatment outcomes [6, 14, 15]. A study in Malawi showed that one of the reasons for changing the HIV treatment regimen was drug stockouts [14]. A study in Ivory Coast found that stockouts caused 9% of the HIV treatment discontinuations and 30% of the treatment alterations.…”
Section: Introductionmentioning
confidence: 99%